Solids, colloids, and the hydrolysis of tetravalent uranium in chloride media - Grambow, B.; Müller, R.; Schild, D.; Gaona, X. (Frontiers in Nuclear Engineering, 2023)
Understanding of the properties of dissolution and precipitation of Uranium under reducing geochemical conditions is important in radioactive waste management and assessments of natural uranium deposits. The mechanism of forming UO2+y from U(VI) and U(IV) containing aqueous solution (1 M NaCl) and the solubilities of the precipitates were studied under well-controlled reducing conditions as a function of pH, particle size, and supersaturation. The results show that tetramer and colloid formation are critical initial steps. Precipitation is not growth-controlled but appears to be nucleation-controlled, with critical nuclei dimensions of one unit cell of UO2. The precipitates were always crystalline, and amorphous UO2 was not observed.